Achieving two policy targets with one policy instrument: Heterogeneous expectations, countercyclical fiscal policy, and macroeconomic stabilization at the effective lower bound - Gilberto Tadeu Lima; Mark Setterfield; Jaylson Jair da Silveira (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2023)
We explore the short-term macrodynamics of stabilization policy at the effective lower bound (ELB) of the nominal interest rate, in an environment characterized by heterogenous and endogenously time-varying private-sector output and inflation expectations driven by evolutionary dynamics. We show that at the ELB, fiscal policy conducted in accordance with a well-specified policy rule is particularly effective for purposes of macroeconomic stabilization. This is because fiscal interventions have both a direct effect on output and inflation (via aggregate demand formation) and an indirect effect on these same target variables, via the management of heterogenous and evolving expectations. As a result of the two channels through which it operates, and seemingly despite the logic of the Tinbergen (targets-instruments) principle, fiscal policy is thus revealed as a single policy instrument capable of achieving two policy goals.
Keywords: E12; E52; E62; E63; E71; 330; Stabilization policy; effective lower bound; fiscal policy; heterogeneous inflation and outputexpectations; satisficing evolutionary dynamics